Literature Review : Transmisi Covid-19 dari Manusia ke Manusia di Asia - Wahyu Dwi Nugroho; Wulandari Indah Cahyani; Alanish Shahnia Tobing; Nur Istiqomah; Intan Cahyasari; Murdewi Indrastuti; Priyo Sugondo; Atyanti Isworo (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
Introduction: The latest corona virus (Covid-19), centered in one of the provinces in China, has spread to various countries. World Health Organization (WHO) Emergency Committee declared a global health emergency. Covid-19 virus based on several studies can be transmitted from human to human. Knowing the ways and media of transmission of Covid-19 is crucial so that transmission prevention can be done immediately. Objective: The purpose of the study to know the specific transmission of Covid-19 virus and how to prevent it that can be done. Method: The research was conducted using two databases, namely: Google scholar and Pubmed 2019-2020. Articles that meet the inclusion criteria namely methods, media of transmission and management of prevention of Covid-19 transmission are then reviewed. Results: Covid-19 transmission from human to human can be caused by close relationships such as family, close relatives, close friends, contact with people who are already infected. Transmission occurs through coughing, sneezing and aerosols. Transmission by air contributed to the Covid-19 outbreak. Less than one meter distance from an infected person has the potential for transmission. In the mechanism of infectious disease, transmission through vomiting plays a greater role than droplets. Discussion: Covid-19 virus has spread to more than 100 countries. Appropriate measures must be taken immediately to prevent the spread of the epidemic. The main purpose of prevention is to break the chain of transmission from human to human by separating people who have the potential to transmit it to others. One effort to achieve these goals is self-isolation at home or in health services. Social restrictions are also important to prevent spread in people who have not been detected by Covid-19. Conclusion: Because of its rapid and wide spread, it is important to prevent proper transmission to avoid threats to health, and the spread of this virus. By knowing Covid-19 transmission can be used as a guide for prevention and control both at home, and in health care.